GP124 IL1- β levels at presentation correlate with symptom burden at 2 weeks in paediatric mild traumatic brain injury. (June 2019) - Ryan, Emer; Kelly, Lynne; Duff, Eimear; Bates, Mark; Bolger, Turlough; Molloy, Eleanor
Abstract : Aims: To evaluate components of the innate immune system, the inflammsome, in mild Traumatic Brain Injury (TBI) and the correlation with symptom burden 2 weeks from injury. We examine activation of the pathway at presentation, and also at 2 weeks from injury compared with healthy control children. Methods: Whole blood was sampled from children with mild TBI within 24 hours of injury and at two weeks from injury and compared to healthy paediatric controls at baseline. RNA was isolated and cDNA was synthesized. Gene Expression of NLRP3 and IL1 β via rtPCR was recorded in 22 patients and 5 controls at baseline and 15 patients at 2 weeks. The Post Concussive Symptom Inventory was administered at 2 weeks. A change from pre-injury baseline was recorded. Results: Inflammasome was upregulated via NLRP3 expression in children with TBI compared to controls across groups however this did not correlate with symptoms at 2 weeks. Higher IL-1β transcription levels at presentation were positively correlated by Pearson correlation (p = 0.029) with higher symptom scores at 2 weeks. Conclusion: Inflammation is altered in TBI compared to controls The NLRP3 component of inflammasome while elevated does not correlate with symptom burden. IL=1 β gene transcription does. IL-1 β holds promise in predicting symptom burden following mTBI. Selective inhibition of systemic inflammation targeting the inflammasome may have a future immunomodulatory role as a target in treating mTBI.